Variação sazonal da população de bactérias e fungos e dos teores de nitrato e amônio do solo nos sítios do LBA e PPBIO, na amazônia oriental - MOURA, Quêzia Leandro de (Universidade Federal do Pará, 2017)
It is possible that the environmental factors determining the behavior of soil microbiota are being modified by anthropic or natural climate change. In order to check the effect of the exclusion of water over the population of bacteria and fungi in the soil, the present study was developed. The chosen location is the area of the ESECAFLOR experiment, which simulates the occurrence of extreme phenomena such as El Niño event, and the area of biodiversity research program Program-PPBio (primary forest). This later area, supposed to be used for studying the Biodiversity of the Amazon, was used as a control area for comparative purposes. The soil was sampled at 00 - 05, 05 -10, 10-20 and 20-30 cm depths, during the rainy, transition and less rainy seasons. The highest values of Colonies Forming Units (CFU) for bacteria and fungi populations were 196 x 104 CFU/g of soil and 124 x 102 CFU/g of solo, respectively, both in the area without human intervention (PPBio). Soil moisture is the variable influencing most the obtained counting values of fungi and bacteria populations.